(untitled) (International Journal of Language, Literacy and Translation, 2025)
This study investigated the neologism manifestations in the communication style of Adamu, also known as Baba-ina-ne, using semantic analysis method. As an individual with speech impairment, Adamu (Baba-ina-ne) does not speak his indigenous language fluently similar to other individuals in his locality. As such he innovated simple and peculiar way of expressing meanings to events and identities, at his capability. The term "neologism" used in the study refers to the creation of new words. The main focus of this study is the phenomena of neologism, which explores how a dialect in the person of Adamu "Baba-ina-ne" comes up with new terms. The three elements of neologism—word generation, borrowing, and coining—form the basis of this paper’s theoretical framework. The use of neologism as a research tool is the foundation of this work. Participant observation, interviews, and the ethnography method were used to gather the data. The research showed that one person could have a significant impact on the development of new terms, which are then adopted by the local population and used in daily speech. Undoubtedly, neologisms offer vivid depictions of a variety of social and cultural acts in the separate societies, and the motivation behind them all is the same: to increase the language's vocabulary.